Analisis Kesulitan Siswa Kelas 2 SD Pada Pembelajaran Operasi Hitung Bilangan Cacah. - Rizky Esti (Jurnal Pendidikan Edutama, 2014)
Difficulty Analysis of Second Graders of Elementary School Students in Learning Counting Operation of Counting Numbers. This study is a qualitative study which is aimed at (1) Determine any difficulties experienced by students in learning addition and subtraction of natural numbers, (2) determine the cause of the difficulties experienced by students in learning the operations of addition and subtraction natural numbers, (3). Knowing how to solve the problems faced by students. The population in this study was 45 elementary school students in Purwosari grade 2. The samples in this study were 2 students taken by simple random sampling. Data collection was performed by the method of documentation, questionnaires, observation and tests. The results showed that: there are many students who are experiencing difficulties in arithmetic operations, especially regarding the sum of natural numbers and a reduction in borrowing store.Keywords: analysis of difficulties, arithmetic operations